Long non-coding RNA H19 regulates endothelial cell aging via inhibition of STAT3 signalling. Issue 1 (13th August 2018) - Hofmann, Patrick; Sommer, Janina; Theodorou, Kosta; Kirchhof, Luisa; Fischer, Ariane; Li, Yuhuang; Perisic, Ljubica; Hedin, Ulf; Maegdefessel, Lars; Dimmeler, Stefanie; Boon, Reinier A
Abstract: Aims: Long non-coding RNAs (lncRNAs) have been shown to regulate numerous processes in the human genome, but the function of these transcripts in vascular aging is largely unknown. We aim to characterize the expression of lncRNAs in endothelial aging and analyse the function of the highly conserved lncRNA H19. Methods and results: H19 was downregulated in endothelium of aged mice. In human, atherosclerotic plaques H19 was mainly expressed by endothelial cells and H19 was significantly reduced in comparison to healthy carotid artery biopsies. Loss of H19 led to an upregulation of p16 and p21, reduced proliferation and increased senescence in vitro . Depletion of H19 in aortic rings of young mice inhibited sprouting capacity. We generated endothelial-specific inducible H19 deficient mice (H19 iEC-KO ), resulting in increased systolic blood pressure compared with control littermates (Ctrl). These H19 iEC-KO and Ctrl mice were subjected to hindlimb ischaemia, which showed reduced capillary density in H19 iEC-KO mice. Mechanistically, exon array analysis revealed an involvement of H19 in IL-6 signalling. Accordingly, intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 were upregulated upon H19 depletion. A luciferase reporter screen for differential transcription factor activity revealed STAT3 as being induced upon H19 depletion and repressed after H19 overexpression. Furthermore, depletion of H19 increased the phosphorylation of STAT3 at TYR705 and pharmacological inhibition of STAT3 activation abolished the effects of H19 silencing on p21 and vascular cell adhesion molecule 1 expression as well as proliferation. Conclusion: These data reveal a pivotal role for the lncRNA H19 in controlling endothelial cell aging.